I follow the Mahatma - Munshi, Kanaiyalal Maneklal, 1887-1971. (Bombay : Allied Publishers, 1940)
Author's personal reactions of Gandhiji and his activities.
Includes index.
Microfilm.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Influence